2008
DOI: 10.3136/fstr.14.457
|View full text |Cite
|
Sign up to set email alerts
|

Application of Whey Protein Isolate Glycated with Rare Sugars to Ice Cream

Abstract: Glycated whey protein isolate (WPI) was prepared by incubation of WPI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…The addition of whey protein isolate (WPI) glycated with the sugars D‐allose and D‐psicose into ice cream has been referred to as a novel way for delivering excellent antioxidant properties together with improving foaming and emulsifying capacity (Puangmanee and others ). The authors suggested that free radical scavenging activity for the specific formulations was associated with the conjugation of Maillard reaction products found in WPI with the C‐3 hydroxyl group of these sugars.…”
Section: Natural Antioxidantsmentioning
confidence: 99%
“…The addition of whey protein isolate (WPI) glycated with the sugars D‐allose and D‐psicose into ice cream has been referred to as a novel way for delivering excellent antioxidant properties together with improving foaming and emulsifying capacity (Puangmanee and others ). The authors suggested that free radical scavenging activity for the specific formulations was associated with the conjugation of Maillard reaction products found in WPI with the C‐3 hydroxyl group of these sugars.…”
Section: Natural Antioxidantsmentioning
confidence: 99%
“…Recently, increasing attention has been paid to the Maillard reaction of psicose with proteins due to the excellent functional properties of its corresponding Maillard reaction products (Sun and others 2005, 2008). Puangmanee and others (2008) found that whey protein glycated by psicose showed an excellent emulsion property and could improve the quality of ice cream. In the report of Sun and others (2004a), the gelling functional property of hen ovalbumin could be enhanced by psicose through the Maillard reaction.…”
Section: Introductionmentioning
confidence: 98%
“…Enhanced color formation as a result of accelerated nonenzymatic browning reactions was observed during the processing of cookies leading to higher antioxidant capacity. [6] In addition to the antioxidant capacity, it was also revealed that, emulsification [7] , foaming capacity, [6] gelling ability, [8] and textural properties [9] of food products noticeably enhanced with the utilization of D-psicose in numerous studies.…”
Section: Introductionmentioning
confidence: 99%